Retrospective Study of the Safety and Efficacy of Anlotinib Combined With Dose-Dense Temozolomide in Patients With Recurrent Glioblastoma - She, Lei; Su, Lin; Shen, Liangfang; Liu, Chao (Frontiers in Oncology, 2021)
Purpose: The purpose of this study was to retrospectively analyze the safety and clinical efficacy of anlotinib combined with dose-dense temozolomide(TMZ) as the first line therapy in the treatment of recurrent glioblastoma (rGBM). Patients and Methods: We collected the clinical data of 20 patients with rGBM. All patients received anlotinib (12 mg daily, orally for 2 weeks, discontinued for 1 week, repeated every 3 weeks) combined with dose-dense TMZ (100 mg/m2, 7 days on with 7 days off) until the disease progressed (PD) or adverse effects(AEs) above grade 4 appeared. Grade 3 AEs need to be restored to grade 2 before continuing treatment, and the daily dose of anlotinib is reduced to 10mg. The patients were reexamined by head magnetic resonance imaging (MRI) every 1-3 months. The therapeutic effect was evaluated according to Response Assessment in Neuro-Oncology (RANO) criteria. The survival rate was analyzed by Kaplan-Meier survival curve analysis. The baseline of all survival index statistics were the start of anlotinib combined with dose-dense of TMZ. National Cancer Institute-Common Terminology Criteria Adverse Events version 4.0 (NCI-CTCAE 4.0) was used to evaluate AEs. Results: Twenty cases of rGBM were evaluated according to the RANO criteria after treatment with anlotinib and dose-dense TMZ, including 5 cases of stable disease (SD), 13 cases of partial response (PR), 1 case of complete response (CR), and 1 case of PD. The median follow-up time was 13.4 (95% CI=10.5-16.3) months. The 1-year overall survival(OS) rate was 47.7%. The 6-month progression-free survival (PFS) rate was 55%. In the IDH wild type group, the median PFS and median OS were 6.1months and 11.9months,respectively. We observed that AEs associated with treatment were tolerable. One patient stopped taking the drug because of cerebral infarction. There were no treatment-related deaths. Conclusion: Anlotinib combined with dose-dense TMZ for the first-line therapy showed good efficacy in OS, PFS, ORR and DCR in the treatment of rGBM, and the AEs were tolerant. Randomized controlled clinical trials investigating the treatment of rGBM with anlotinib are necessary.